Autoimmune Anemia in Malaria. Issue 2 (February 2020) - Rivera-Correa, Juan; Rodriguez, Ana
Abstract : Severe anemia is a major cause of death by malaria. The loss of uninfected erythrocytes is an important contributor to malarial anemia; however, the mechanisms underlying this pathology are not well understood. Malaria-induced anemia is related to autoimmune antibodies against the membrane lipid phosphatidylserine (PS). In mice, these antibodies induce the clearance of uninfected erythrocytes after binding to PS exposed in their membrane. In human malaria patients there is a strong correlation between anemia and anti-PS antibodies. During malaria, anti-PS antibodies are produced by atypical B cells, whose levels correlate with the development of anemia in patients. Autoimmune responses, which are documented frequently in different infections, contribute to the pathogenesis of malaria by inducing the clearance of uninfected erythrocytes. Highlights: Autoimmune antibody responses against PS generated during malaria contribute to anemia. Anti-PS antibodies recognize uninfected erythrocytes during malaria and facilitate their clearance through opsonization or hemolysis. Similarly to some autoimmune disorders, during malaria, atypical B cells are activated through inflammatory signals, such as interferon (IFN)-γ, and the activation of Toll-like receptor 9 (TLR-9) by parasite DNA. Levels of atypical memory B cells correlate with anti-PS antibodies and anemia in malaria patients. Atypical memory B cells (AtMBCs) are able to secrete antibodies against parasite and autoimmune antigens.